Between solidarism and business management: assessing management factors for social enterprise: a survey in Italy. Issue 1 (2014) - ,; ,
Abstract : Purpose – The aim of this paper is to investigate the management dimensions and factors of social enterprise, in order to identify valuable management innovation challenges. Given the deep social changes occurring, and strong public spending reviews, social enterprises are called to a shift from a traditional management model based on solidarity to a business oriented one. Design/methodology/approach – The research is based on a survey administered to 344 enterprises, based in five regions of south Italy, with a response of 67 social enterprises. After a first round of six open interviews administered to social entrepreneurs, a closed questionnaire was designed and administered through web survey tools to the 344. Findings – The paper investigates social enterprises, with particular regard to the social cooperatives, identifying and assessing the management dimensions and factors constituting their management model. The analysis reveals and addresses management challenges helpful in driving a competitive growth of social enterprises. Originality/value – The paper explores a sector slightly investigated by management literature, and usually focused by the social literature. Collective interest, social value, mutualism, solidarity appear to be gaps in today's management models, contributing to financial crisis, employment crisis, social emergencies. Social enterprise may represent a new management model, revealing dimensions and factors of interest for a new business management, until it is supported with a more business management oriented model.